Climate Change: National and Local Policy Opportunities in China - Fei Teng; Alun Gu (Fondazione Eni Enrico Mattei (FEEM), 2007)
Climate Change poses a wide range of potentially very severe threats in China. This aggravates the existing vulnerability of China and is one of the big challenges faced by the Chinese government. Adaptation programmes and projects are being developed and implemented at national and local level. As China is engaged in heavy investment in infrastructure development as a consequence of the rapid process of development and urbanization, mainstreaming adaptation into such development process is a priority for China. China has also made positive contributions to reducing greenhouse gas emissions through participations in the CDM under the Kyoto Protocol framework. Although mitigation is not a priority at national or local level, it has been integrated into national and local development plans explicitly. This paper addresses the following questions: What is the policy space for climate change mitigation and adaptation policy at national and local level and what is already being done? The three case studies at local level - Beijing, Guangdong and Shanghai presented here, highlight the local benefits in terms of local pollution of integrating mitigation policies into local development. However, financial constraints usually prevent such a positive policy integration. National policies and international cooperation aiming at bridging the financial gap and promoting technology transfer would help in integrating local pollution control and mitigation efforts in China today.
Keywords: H7; Q54; Q56; O53; 330; Climate Change; Local Policy; National Policy; Mitigation; Local Pollution